Risk of harm to others: subjectivity and meaning of risk in mental health practice. Issue 10 (3rd October 2021) - Nathan, Rajan; Whyler, Jonathon; Wilson, Peter
Abstract: In everyday mental health practice, clinicians are expected to assess and manage the risk of harm that may be caused by their patients to others. An informed approach to the activities of risk assessment and management should be grounded in a thorough understanding of the notion of risk. Whilst there are agreed definitions of risk, they do not do justice to the complexity of in-vivo representations of risk. Based on a review of the literature, an analysis of clinical guidelines, and practicing psychiatrists' reflections on their own clinical experiences and sample vignettes, this article explores the varied subjective representations of risk in mental health practice. Of specific relevance to the possibility of an individual causing harm is the need to recognise that the causal agent of harm is an as-yet-unrealised state of consciousness, and that actions that may reduce risk are multiple and have effects that are difficult to define in advance. From an analysis of the semantic context of the use of the word 'risk' within practice guidance, the authors demonstrate a wide range of meanings (including harm, possibility of harm, characteristics of possible harm, a state with changeable potential for harm, and different states of potential harm) with different degrees of embodiment. With reference to clinical scenarios, the formation of individual subjective representations of risk are shown to vary not only in the way they can be characterised (e.g. likelihood, severity, and imminence), but also in the extent to which they come into subjective focus. Uncovering the different ways risk is represented in practice should allow a more refined approach to guiding and studying the process of risk assessment and management.